Investigasi Proses Fonologis Dalam Bahasa Madura Dialek Bangkalan: Pendekatan Generatif Transformasional - Ika Susanti (Jurnal Pendidikan dan Sastra Inggris, 2023)
This paper discussed the phonological process of the Madurese dialect of Bangkalan. The Madurese language has 5 different dialects, namely the Madurese dialect of Bangkalan, Sumenep, Pamekasan, Sampan, and Kangean. The division of dialects is based on the number of areas on the island of Madura. Each dialect has its own characteristics and uniqueness. The focus of this research is how the phonological process that occurs in the Madurese grammar of the Bangkalan dialect. Furthermore, transformational generative was used as a theory in this research. The findings of this study, there are four phonological processes that occur in the Madurese dialect of Bangkalan, namely assimilation, deletion, main class change, and syncope.